Nanny goat and the seven little kids - Kimmel, Eric A.; Stevens, Janet; Grimm, Jacob; Grimm, Wilhelm (Holiday House, 1990)
Mother goat rescues her seven kids after they are swallowed by a wicked wolf.
Mother goat rescues her seven kids after they are swallowed by a wicked wolf.
Keywords: Folklore / Germany / Juvenile literature. / http://id.loc.gov/authorities/subjects/sh85050118; Fairy tales. / http://id.loc.gov/authorities/subjects/sh85046925